The Zn(II)2Cys6-Type Transcription Factor ADA-6 Regulates Conidiation, Sexual Development, and Oxidative Stress Response in Neurospora crassa - Sun, Xianyun; Wang, Fei; Lan, Nan; Liu, Bo; Hu, Chengcheng; Xue, Wei; Zhang, Zhenying; Li, Shaojie (Frontiers in Microbiology, 2019)
Conidiation and sexual development are critical for reproduction, dispersal and better-adapted survival in many filamentous fungi. The Neurospora crassa gene ada-6 encodes a Zn(II)2Cys6-type transcription factor, which deletion resulted in reduced conidial production and female sterility. In this study, we confirmed the positive contribution of ada-6 to conidiation and sexual development by detailed phenotypic characterization of its deletion mutant and the complemented mutant. To understand the regulatory mechanisms of ADA-6 in conidiation and sexual development, transcriptomic profiles generated by RNA-seq from ∆ada-6 mutant and wild type during conidiation and sexual development were compared. During conidial development, differential expressed genes (DEGs) between ∆ada-6 mutant and wild type are mainly involved in oxidation-reduction process and single-organism metabolic process. Several conidiation related genes are positively regulated by ADA-6, such as fluffy and acon-3 that positively regulate conidiation, and genes preferentially expressed during conidial development (eas, con-6, con-8, con-10, con-13, pcp-1 and NCU9357), as the expression of these genes were lower in ∆ada-6 mutant than that in wild type during conidial development. Phenotypic observation of deletion mutants for other genes with unknown function down-regulated by ada-6 deletion revealed that deletion mutants for 4 genes (NCU00929, NCU05260, NCU00116 and NCU04813) produced less conidia than wild type. Deletion of ada-6 resulted in female sterility, which might be due to that ADA-6 affects oxidation-reduction process and transmembrane transport process, and positively regulates the transcription of pre-2, poi-2 and NCU05832, three key genes participating in sexual development. In both conidiation and the sexual development process, ADA-6 regulates the transcription of cat-3 and genes participating in reactive oxygen species (ROS) production according to RNA-seq data, indicating a role of ADA-6 in oxidative stress response. This was further confirmed by the results that deletion of ada-6 led to hypersensitivity to oxidants H2O2 and menadione. Together, these results proved that ADA-6, as a global regulator, plays a crucial role in conidiation, sexual development and oxidative stress response of N. crassa.